Equilibrium leaching of selected ultraviolet stabilizers from plastic products - Ngoc Do, Anh T.; Ha, Yeonjeong; Kang, Hyun Joong; Kim, Ju Min; Kwon, Jung Hwan (Journal of Hazardous Materials, 2022)
Despite the importance of (micro)plastics in the release of plastic additives, the leaching mechanism of organic plastic additives from various plastic materials is poorly understood. In this study, the equilibrium leaching of five highly hydrophobic ultraviolet (UV) stabilizers (UV326, UV327, UV328, UV329, and UV531) from three plastics (low-density polyethylene (LDPE), polyethylene terephthalate (PET), and polystyrene (PS)), was investigated employing acetonitrile-water cosolvent systems. Their extrapolated water solubilities were in the 0.15–0.54 μg L−1 range, limiting their transport as “dissolved” in water and (micro)plastics are likely those particulate carriers. The equilibrium leaching of UV stabilizers from plastics was better explained by the Flory-Huggins model incorporating the nonideal behavior caused by the size disparity between UV stabilizers and polymer materials and their compatibility. Specifically, leaching of UV stabilizers from LDPE showed a positive deviation from Raoult's law, whereas slight negative deviations were observed in PET and PS. In addition, the equilibrium concentration of the benzotriazoles in LDPE increased linearly with the volume fraction up to only 0.4%. These observations could be explained by the unfavorable interactions of UV stabilizers with polyethylene, indicating that polymer type should be also important when evaluating the fate of hydrophobic additives. Because equilibrium distribution of additives between (micro)plastics and water is crucial for evaluating the fate and transport of hydrophobic plastic additives, further studies on the leaching equilibrium of various additives from different plastic materials are necessary.
Keywords: Benzotriazoles; Flory-Huggins model; Hydrophobics; Leaching mechanism; Micro plastics; Microplastics; Passive dosing; Plastic additives; Plastic materials; Ultraviolet stabilizers; Plastics; Polyethylene; Polymers; Polystyrenes; Water Pollutants, Chemical; Benzotriazoles; Flory-Huggins model; Microplastics; Passive dosing; Plastic additives